Improving The Process Of Regulating The Activities Of Commercial Banks Through Money-Credit Instruments (Eurasian Journal of Learning and Academic Teaching, 2022)
The practice of using monetary policy instruments plays an important role in regulating the activities of commercial banks. The implementation of a restrictive monetary policy by the central bank could have a strong negative impact on the liquidity of commercial banks. The article identifies current issues related to improving the practice of regulating the activities of commercial banks through the instruments of monetary policy pursued by the Central Bank of the Republic of Uzbekistan and develops scientific proposals to address them.